How Does CEO Career Origin Influence Firm’s Risk-Taking? - Chahyadi, Candra; Wineka, Pamitra (Journal of Accounting and Finance, 2019)
Does CEO career origin matter for corporate risk-taking? Is the level of corporate risk-taking determined by firm characteristics or by CEO personal/compensation characteristics? Using 3,006 CEO turnover data between 1992 and 2010, we find that outsider CEOs make more risky investment decisions than insider CEOs. After controlling for compensation sensitivity variables, we find that outsider CEOs are more risk-taking than insider CEOs. The board of directors may hire outsider CEOs because of the risk-taking reason. Our results also suggest that the CEO compensation structure difference is not the reason why outsider CEOs take more risk than insider CEOs.